2004
DOI: 10.1897/03-540
|View full text |Cite
|
Sign up to set email alerts
|

Chemical speciation and cellular deposition of lead in Sesbania drummondii

Abstract: The internalized speciation of lead in roots and leaves of Sesbania drummondii, a lead hyperaccumulator, grown in lead nitrate solution was studied using x-ray absorption near-edge structure and extended x-ray absorption fine structure. Lead was predominantly present as lead acetate in both plant tissues. The other dominant forms of accumulation were lead-sulfur compounds. Whereas lead sulfate and sulfide were found in leaves, only lead sulfide was detected in root samples. These observations indicate that S. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 29 publications
3
30
0
1
Order By: Relevance
“…The localization of Pb ions mainly observed in the root xylem suggests that it is the main pathway of Pb transport from root to shoot. Similar observations were also reported by Sharma et al ([2004]).…”
Section: Discussionsupporting
confidence: 92%
“…The localization of Pb ions mainly observed in the root xylem suggests that it is the main pathway of Pb transport from root to shoot. Similar observations were also reported by Sharma et al ([2004]).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are compatible to the earlier studies using alfalfa plants in respect of XANES spectra (9) but unique in LC-XANES features. LC-XANES fittings have been used to identify the different species of metals present in plants with a high degree of certainty (9,14).…”
Section: Resultsmentioning
confidence: 99%
“…4) however, Shao et al (2007) showed that Cd-induced oxidative stress in rice is alleviated by Fe. Fe is an integral cofactor of antioxidant enzymes such as catalase and ascorbate peroxidase (Sharma et al 2004). As such, the maintenance of high levels of Fe in the roots when Cd concentrations were highest can increase the activity of these enzymes, and would be an important defense mechanism against ROS generated by Cd-stress (Wang et al 2013).…”
Section: Micronutrient Contentsmentioning
confidence: 99%